2011
DOI: 10.1002/icd.682
|View full text |Cite
|
Sign up to set email alerts
|

Maternal positive parenting style is associated with better functioning in hyperactive/inattentive preschool children

Abstract: Many preschoolers are highly inattentive, impulsive, and hyperactive; but only some are impaired in their functioning. Yet factors leading to functional impairment, above and beyond the severity of inattentive and hyperactive symptoms, have not been systematically examined. This study examined a model suggesting that after controlling for attention-deficit/hyperactivity disorder (ADHD) symptom severity, child temperament is uniquely associated with parenting stress; that parenting stress affects parenting styl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 33 publications
5
33
2
4
Order By: Relevance
“…Also, Taylor, Wilson, Slater, and Mohr (2011) found that style dimensions of demandingness and responsiveness were associated with healthy weight-related attitudes in children. High levels of positive parenting were associated with better child functioning as also found (Healey, Flory, Miller, & Halperin, 2011), while the use of corporal punishment as a disciplinary mean increases the impairment caused by feeding problems. Research has also suggested that parental practices such as warmth/connection in combination with parental structure/rules are associated with fewer disordered eating behaviors in adolescents (Enten & Golan, 2009).…”
Section: Discussionsupporting
confidence: 55%
“…Also, Taylor, Wilson, Slater, and Mohr (2011) found that style dimensions of demandingness and responsiveness were associated with healthy weight-related attitudes in children. High levels of positive parenting were associated with better child functioning as also found (Healey, Flory, Miller, & Halperin, 2011), while the use of corporal punishment as a disciplinary mean increases the impairment caused by feeding problems. Research has also suggested that parental practices such as warmth/connection in combination with parental structure/rules are associated with fewer disordered eating behaviors in adolescents (Enten & Golan, 2009).…”
Section: Discussionsupporting
confidence: 55%
“…In this context, we found that parental involvement in school was significantly connected to mathematical achievements, but only among children with special needs whose parents were authoritarian. While this finding supports the assumption of the moderating role of parenting style in general, it essentially contradicts the rationale regarding the protective and beneficial effect of the authoritative parenting style, in contrast with that of the authoritarian parenting style, derives from several works who dealt with the relationship between parenting practices and children's well-being (e.g., Barkauskiene, 2009;Blondal & Adalbjamardottir, 2009;Healey et al, 2011;Steinberg et al, 1992;Yaffe & Burg, 2013). This finding has yet to be reported in this specific form in the research literature, although there is some empirical evidence indicating the possibility that authoritarian parenting may be related to several aspects of successful academic functioning among children (Gonzalez, Greenwood & Hsu, 2001;Kazmi, Sajjid & Pervez, 2011), and even in the context of mathematical studies (Gonzalez & Walters, 2006).…”
Section: Journal Of Studies In Educationcontrasting
confidence: 55%
“…This is because in such cases the adoption of a parenting style relies more on the child's characteristics and not just on the parent's characteristics (Woolfson & Grant, 2005). Most of the studies about children with ADHD, for example, show that the parents' characteristics moderate the influence of the children's characteristics on their development and adaptation to the various circles of life (Deault, 2010;Gau & Chang, 2013;Healey, Flory, Miller & Halperin, 2011;Kaiser, McBurnett & Pfiffner, 2011;Modesto-Lowe, Danforth & Brooks, 2008). Raising children with ADHD involves great mental stress and difficulty, which project onto the parental functioning and style, and this in turn is related to the children's functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En la práctica clínica los resultados constituyen un aporte para la intervención con dichas familias, al resaltar la importancia de favorecer el desarrollo de técnicas efectivas de disciplina y una adecuada comunicación y afecto en la relación de las madres con sus hijos; asimismo, proporcionarle a estas madres recursos en materia de estrategias de afrontamiento que amortigüen los efectos estresantes de la crianza y convivencia con niños que presentan dicho trastorno (Martínez, 2010;Healey, Flory, Miller y Halperin, 2011;Figueroa, Aburto y Acevedo, 2012). Incrementar el conocimiento acerca de cuáles son aquellas estrategias de afrontamiento al estrés más efectivas, y bajo qué circunstancias pueden ser más beneficiosas para estas madres, tiene una implicación directa sobre el tratamiento del trastorno (Lyons, Leon, Phelps y Dunleavy, 2010), precisamente porque las estrategias y los estilos de afrontamiento que utilicen las madres frente a las situaciones de crisis podrían jugar un rol importante en el curso de la enfermedad de su hijo.…”
Section: Discussionunclassified